The Effect of Diluted Penetration Enhancer in Nebulized Mist versus Liquid Drop Preparation Forms on Retrobulbar Blood Flow in Healthy Human Subjects - Ruta Barsauskaite; Lina Siaudvytyte; Annahita Amireskandari; Patrick Egan; Austin Gerber; Brent Siesky; Ingrida Januleviciene; Sally Primus; Alon Harris (MDPI AG, 2012)
The aim of this study was to compare the effects of nebulized mist and liquid drop applications on retrobulbar blood flow. A prospective, non-randomized clinical trial was used to collect data from 40 healthy human eyes. Color Doppler Imaging determined peak systolic (PSV) and end diastolic (EDV) blood flow velocities and resistance index (RI) in the ophthalmic artery after both applications. Measurements were taken at baseline and at 1 min post-treatment in both eyes with 5 min measurements in the treatment eye only. p values ≤ 0.05 were considered statistically significant. Mist application to treatment eye produced an increase in 1 min and 5 min PSV and EDV (0.001 < p < 0.03) and a decrease in 5 min RI (p = 0.01), with no significant changes in PSV, EDV or RI of control eye or in treatment eye 1 min RI (p > 0.05). Drop application to treatment eye produced an increase in PSV (p < 0.001) and EDV (p = 0.01) at 1 min, with an increase in control eye 1 min PSV and EDV (p = 0.03). There were no statistically significant changes in treatment eye PSV, EDV and RI after 5 min (p > 0.05). The use of nebulized mist may provide an effective alternative to liquid drop medication application.